EFFECT OF SERVICE MARKETING MIX ON HOSPITAL SELECTION MEDIATED WITH BRAND IMAGE ON HOSPITAL'S OUTPATIENTS - anik setyowati; Djawoto Djawoto; Hendri Soekotjo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aimed to analyze and empirically test the influence of products, prices, locations, promotions, people, processes, physical evidence against the selection of brand-mediated hospitals in new outpatients of Sumberglagah Hospital, Mojokerto, East Java. This research was quantitative with the type of causality and population research was new patient outpatient Sumberglagah Hospital, about 5,087. Samples were 100 people with purposive sampling. Its analysis technique applied path analysis. Therefore, the hypothetical test resulted that product, price, location, promotion, person, process, and physical evidence positively and significantly affected the brand image. Products, prices, locations, promotions, people, processes, and physical evidence positively and significantly affected hospital selection. The brand image had a positive and significant influence on the selection of hospitals. Moreover, the brand image could mediate product relationships, prices, locations, promotions, people, processes, and physical evidence against hospitals' selection through brand image. Keywords: product, price, location, promotion, people, process, physical evidence, brand image, and purchasing decision.